(untitled) (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2020)
Pandemics occur in the world, all countries experience shocks by the presence and spread of a virus, namely covid-19. So that the virus does not spread more widely, especially in Indonesia, it needs to be handled and handled well. The purpose of this study is to analyze, and interpret a simulation of a mathematical model of the spread of the covid-19 virus with cure rates and infection with the virus. In the preparation of the model obtained mathematical models. From the model obtained a range of percentage of virus spread with a cure rate, I (n) <1. The results of the modeling show the virus spread will gradually decrease from the population.